6x-y=7

Subtract 6x from both sides of the equation.

-y=7-6x

Multiply each term in -y=7-6x by -1

Multiply each term in -y=7-6x by -1.

(-y)⋅-1=7⋅-1+(-6x)⋅-1

Multiply (-y)⋅-1.

Multiply -1 by -1.

1y=7⋅-1+(-6x)⋅-1

Multiply y by 1.

y=7⋅-1+(-6x)⋅-1

y=7⋅-1+(-6x)⋅-1

Simplify each term.

Multiply 7 by -1.

y=-7+(-6x)⋅-1

Multiply -1 by -6.

y=-7+6x

y=-7+6x

y=-7+6x

y=-7+6x

Choose any value for x that is in the domain to plug into the equation.

Remove parentheses.

y=-7+6(0)

Simplify -7+6(0).

Multiply 6 by 0.

y=-7+0

Add -7 and 0.

y=-7

y=-7

Use the x and y values to form the ordered pair.

(0,-7)

(0,-7)

Remove parentheses.

y=-7+6(1)

Simplify -7+6(1).

Multiply 6 by 1.

y=-7+6

Add -7 and 6.

y=-1

y=-1

Use the x and y values to form the ordered pair.

(1,-1)

(1,-1)

Remove parentheses.

y=-7+6(2)

Simplify -7+6(2).

Multiply 6 by 2.

y=-7+12

Add -7 and 12.

y=5

y=5

Use the x and y values to form the ordered pair.

(2,5)

(2,5)

These are three possible solutions to the equation.

(0,-7),(1,-1),(2,5)

Find Three Ordered Pair Solutions 6x-y=7